Christian Universities Grow in Africa - Carpenter, Joel (International Higher Education, 2017)
Christian higher education is expanding rapidly in Africa, following the growth of Christian populations on the continent. Although dynamic, these universities face the same problems of resources, standards, and other that confront African universities generally.